Fruits and vegetables are incorporated into home cuisine in different ways that are relevant to promoting increased consumption - Penny, Mary E.; Meza, Krysty S.; Creed-Kanashiro, Hilary; Marin, R. Margot; Donovan, Jason (Wiley, 2017)
Fruits and vegetables are essential for healthy life. We examined the fruits and vegetables consumption by 240 caregivers and their children aged 1–17 years in peri‐urban Lima, and the ways that they were incorporated into local cuisine. A randomized cross‐sectional household survey collected information on the weight of all foods eaten the previous day (24 h) including fruits and vegetables, their preparation and serving sizes. Fruit and vegetable consumption was low and very variable: fruit intake was mean 185.2 ± 171.5 g day−1, median 138 g day−1 for caregivers and 203.6 ± 190.6 g day−1 and 159 g day−1 for children, vegetable intake was mean 116.9 ± 94.0 g day−1 median 92 g day−1 for caregivers, mean 89.3 ± 84.7 g day−1 median 60 g day−1 for children. Only 23.8% of children and 26.2% of caregivers met the recommended ≥400 g of fruit or vegetable/day. Vegetables were mainly eaten either as ingredients of the main course recipe, eaten by about 80% of caregivers and children, or as salads eaten by 47% of caregivers and 42% of children. Fruits were most commonly eaten as whole fresh fruits eaten by 68% of caregivers and 75% of children. In multivariate analysis of the extent to which different presentations contributed to daily fruit and vegetable consumption, main courses contributed most to determining vegetable intake for caregivers, and for children, main course and salads had similar contributions. For fruit intake, the amount eaten as whole fruit determined total fruit and total fruit plus vegetable intake for both caregivers and children. Local cuisine should be considered in interventions to promote fruit and vegetable consumption. © 2016 John Wiley & Sons Ltd